Nanotechnology Advances in the Detection and Treatment of Cancer - Miglani, Kanika; Kumar, Lalit (Disease and Health Research: New Insights Vol. 8, 2024)
Cancer is a life-threatening disease due to which more than ten million people worldwide lose their lives per year. Cancer has many different causes, and prognostic information varies from patient to patient due to the unique molecular characteristics of the human body. However, genetic variability caused by different cancer types and neoplastic alterations makes diagnosis and treatment challenging. Since targeted drug delivery helps patients receive medication by gradually raising drug concentrations in specific body regions, it is regarded as a crucial component of precision medicine in the treatment of cancer. Nanoparticles (NPs) mediated drug delivery can improve local drug delivery systems. Diagnostic tests using NPs enable the identification of biomarkers that accumulate at specific cancer sites, ensuring precise drug delivery planning. However, Nanoparticles can cause immunological reactions and toxicities such as anemia, neutropenia, thrombosis, and allergic reactions. The main purpose of this study is to emphasize the role of nanotechnology in developing novel formulations for cancer treatment.